Analisis Supervisi Pengajaran - Elpaini Elpaini; Dhi Bramasta (Proceedings Series on Social Sciences & Humanities, 2024)
Teaching supervision is a critical aspect of effective school leadership. A school principal who is competent in teaching supervision has the ability to understand individual teacher needs and challenges, and is able to provide the necessary support and guidance. Teaching supervision is not only limited to assessing performance, but also involves efforts to improve teaching skills and student learning outcomes. Good supervision methods involve regular classroom observations, providing constructive feedback, and providing additional training or resources when needed. In addition, a school principal who is effective in teaching supervision must be able to create an environment where teachers feel supported and appreciated, so that teachers are motivated to continue to improve the quality of teaching.